An integrated knowledge framework for industrial product-costing. - Mishra, Karen Eileen (Cranfield University, 2009)
Product-costing is recognised as being erroneous. This thesis examined the background to this inaccuracy through the undertaking of case studies in a range of industrial contexts, in particular the automotive and aerospace industries. Initial research and analysis of the costing literature identified distinctive engineering and economic perspectives underpinning the process. The thesis argues partly that it is the emphasis on these positions and the inadequate attention to human and cultural factors, such as communication, that have contributed to deficient costing processes. To address this a second phase of research was undertaken along side an analysis of human factors literature, to establish where and how qualitative changes might be made to improve organisational product-costing. Social and environmental issues were observed as being ubiquitous to the costing process generically; and subsequently needed to be considered on an interdependent basis alongside the physical, explicit components. The thesis presents an integrated cost-knowledge framework (ICKF), derived from the combined findings of industrial examinations, coupled with cost and cultural literatures. The research phases originally produced six main themes, which referred to the primary concerns correlated to the process, both physically and humanistically; they included issues surrounding: Resource, Data / Information, Comprehension and Training needs. These cost-themes directly related to the cost-knowledge framework. The latter comprises of eight identified knowledge types, recognised to be essential in compiling a cost; all of which are interlinked, incorporating: Costing Process knowledge; knowledge of Design, Materials, Risk, the Product, and Manufacturing Process, all in juxtaposition with Communication and Organisational Cultural knowledge. Hence the themes and knowledge framework focused on an amalgamated costing perception, of both the implicit and explicit aspects of the process. This lead to a question of the lateral dissemination of this Industrial Integrated Cost-Knowledge Framework, ICKF, via proposed costfocused training. In order to develop costing in this broader, inclusive context the training was designed to tackle softer, ‘social’ and ‘human issues’ by incorporating them within the programme, fused with the tangible, technical components of the cost-process. With research participation constituting 25 international organisations, the industrial implementation of the ICKF via targeted, specifically formulated training will assist in addressing the challenges currently experienced within the process of product-costing.